2020
DOI: 10.1002/phar.2445
|View full text |Cite
|
Sign up to set email alerts
|

The Cardiovascular Effects of Treatment with Hydroxychloroquine and Azithromycin

Abstract: Hydroxychloroquine combined with azithromycin has been investigated for activity against coronavirus disease 2019 (COVID‐19), but concerns about adverse cardiovascular (CV) effects have been raised. This study evaluated claims data to determine if risks for CV events were increased with hydroxychloroquine alone or combined with azithromycin. We identified data from 43,752 enrollees that qualified for analysis. The number of CV events increased by 25 (95% confidence interval [CI]: 8, 42, p=0.005) per 1000 peopl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 22 publications
1
5
0
Order By: Relevance
“…Recent studies (25)(26)(27)(28), as well as earlier case reports (29,30), have shown QTc prolongation with HCQ or CQ at conventional doses used to treat rheumatic disease. In a Veterans Administration study of >800 patients with rheumatic disease (90% male and 10% female) seen between 2000 and early 2020 who were taking HCQ and had available ECG data, HCQ was associated with QTc (80) and is reflected on the surface ECG as the T wave.…”
Section: Clinical Experience With Hcq/cq the Qt Interval And Torsade De Pointesmentioning
confidence: 96%
See 2 more Smart Citations
“…Recent studies (25)(26)(27)(28), as well as earlier case reports (29,30), have shown QTc prolongation with HCQ or CQ at conventional doses used to treat rheumatic disease. In a Veterans Administration study of >800 patients with rheumatic disease (90% male and 10% female) seen between 2000 and early 2020 who were taking HCQ and had available ECG data, HCQ was associated with QTc (80) and is reflected on the surface ECG as the T wave.…”
Section: Clinical Experience With Hcq/cq the Qt Interval And Torsade De Pointesmentioning
confidence: 96%
“…A review of the World Health Organization (WHO) pharmacovigilance database from 1967 through March 1, 2020 showed increased reports of QTc prolongation with both HCQ and azithromycin, with more frequent reporting of prolonged QTc and/or TdP/ventricular tachy cardia with the combination of these 2 medications (odds ratio 2.48 [95% CI 1.28-4.79]) (27). In a commercial claims database analysis of events from 2001 through 2017, after 5 days of HCQ therapy the incidence of cardiac events (including myocardial infarction [MI], cerebrovascular accident/transient ischemic attack, sudden death, and arrhythmia) in 2001-2017 among women ages 60-79 years was 0.92 per 1,000 (28). Among those receiving both HCQ and azithromycin, the rate was 4.78 per 1,000 patients (28).…”
Section: Clinical Experience With Hcq/cq the Qt Interval And Torsade De Pointesmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to MG, the proarrhythmic effects of hydroxychloroquine which is prescribed for COVID-19, should also be considered as a possible cause of SCD. QT prolongation and torsades de pointes are common cardiac adverse effects of hydroxychloroquine [18]; nevertheless, the absolute risk of hydroxychloroquine causing SCD is minor and mainly observed among patients older than 60 years of age [19]. We did not have the ECG of the patient prior to his death, however, initial EKG (electrocardiography) was normal and did not show QT prolongation and torsades de pointes.…”
Section: Discussionmentioning
confidence: 87%
“…Male gender and older age were closely associated with developing serious CVS events, which increased with age. A study done by Simmering et al, reported similar outcomes where patients more than 60 years were more prone to develop CVS ADEs as compared to younger ones50 . Yang et al, in their study Clinicaltrial.gov" website, only five trials had reported their results, and 257 studies were without results.…”
mentioning
confidence: 83%